A new homogeneity index definition for evaluation of radiotherapy plans. Issue 11 (12th October 2019) - Yan, Lingling; Xu, Yingjie; Chen, Xinyuan; Xie, Xin; Liang, Bin; Dai, Jianrong
Abstract: Purpose: The goal of this study was to define a new homogeneity index (HI) to evaluate dose homogeneity within a target volume. Materials and Methods: The new HI is based on the area under an ideal dose‐volume histogram curve (IA), the area under the achieved dose‐volume histogram curve (AA), and the overlapping area between the IA and AA (OA). It is defined as the ratio of the square of OA to the product of the IA and AA. To evaluate the performance of the new HI, 88 cases were selected and two plans were designed for each case. The homogeneity of the two plans was first evaluated by three physicists, with their judgments forming the evaluation standard and then evaluated by the new HI and other HIs of D max / Dp, D 5 / D 95, ( D 2  −  D 98 )/ Dp, ( D 2  −  D 98 )/ D 50 and S‐index. An evaluation was determined to be accurate if its result was agreed upon by physicists. The percentage accuracy of evaluation was calculated as the ratio of the number of accurate evaluations to the total number of evaluations. Pearson's chi‐square test was performed for statistical analysis. Results: The percentage accuracies of the new HI, D max / D p, D 5 / D 95, ( D 2  −  D 98 )/ Dp, ( D 2  −  D 98 )/ D 50, and S‐index were 98.51%, 88.80%, 94.78%, 94.78%, 96.27%, and 97.01%, respectively. The newly defined HI had the highest accuracy of all the HIs, with the difference being statistically significant ( P  < 0.05). Conclusions: The newly defined HI was shown to be effective in the evaluation of dose homogeneity, and we recommended it for evaluating the homogeneity of radiotherapy plans.